Mineral fibres, fibrosis, and asbestos bodies in lung tissue from deceased asbestos cement workers. - Albin, M (1990)
Lung tissue from 76 deceased asbestos cement workers (seven with mesothelioma) exposed to chrysotile asbestos and small amounts of amphiboles, has been studied by transmission electron microscopy, together with lung tissue from 96 controls. The exposed workers with mesothelioma had a significantly higher total content of asbestos fibre in the lungs than those without mesothelioma, who in turn, had higher concentrations than the controls (medians 189, 50, and 29 x 10(6) fibres/g (f/g]. Chrysotile was the major type of fibre. The differences were most pronounced for the amphibole fibres (62, 4.7, and 0.15 f/g), especially crocidolite (54, 1.8 and less than 0.001 f/g), but were evident also for tremolite (2.9, less than 0.001, and less than 0.001 f/g) and anthophyllite (1.7, less than 0.001, and less than 0.001 f/g). For amosite, there was no statistically significant difference between lungs from workers with and without mesothelioma; the lungs of workers had, however, higher concentrations than the controls. Strong correlations were found between duration of exposure and content of amphibole fibres in the lungs. Asbestos bodies, counted by light microscopy, were significantly correlated with the amphibole but not with the chrysotile contents. Fibrosis was correlated with the tremolite but not the chrysotile content in lungs from both exposed workers and controls. Overall, similar results were obtained using fibre counts and estimates of mass.